"Since I Must Please Those Below"1: Human Skeletal Remains Research and the Law. Issue 4 (November 2015) - Holland, Thomas D.
The ethics of non-invasive scientific research on human skeletal remains are poorly articulated and lack a single, definitive analogue in western law. Laws governing invasive research on human fleshed remains, as well as bio-ethical principles established for research on living subjects, provide effective models for the establishment of ethical guidelines for non-invasive research on human skeletal remains. Specifically, non-invasive analysis of human remains is permissible provided that the analysis and collection of resulting data (1) are accomplished with respect for the dignity of the individual, (2) do not violate the last-known desire of the deceased, (3) do not adversely impact the right of the next of kin to perform a ceremonious and decent disposal of the remains, and (4) do not unduly or maliciously violate the privacy interests of the next of kin.